Effects of Collaborative Learning on Chemistry Students’ Academic Achievement and Anxiety Level in Balancing Chemical Equations in Secondary School in Katsina Metropolis, Nigeria - Yusuf, Sabiru Dahiru (Journal of Education and Vocational Research, 2014)
The study investigated effects of Collaborative learning on Chemistry students’ academic achievement and Anxiety level in Balancing Chemical Equations in Secondary Schools in Katsina metropolis, Nigeria. The study sampled 80 SSII students, randomly selected from two senior secondary schools in katsina metropolis. The two schools were randomly placed as experimental and control groups each with 40 students. A quasi-experimental pretest-posttest research design was used for the study. The study subjects in the experimental group was taught/ allowed to learn using Collaborative learning concept of Balancing Chemical Equation, while the control group also was taught the same concept using traditional method for the period of six weeks. A chemistry Achievement test and Students Anxiety scale Questionnaire were used as the instruments for data collection. Performance of the two groups were compared using post-test mean scores, and t-test unrelated sample, at a significant level (P) =0.05. The findings from the study shows those students taught using Collaborative learning tent to achieve significantly higher and their anxiety was found to be low when compared with those taught using lecture method. Based on the findings, the recommendations were made among which; Chemistry teachers should always use Collaborative learning in teaching chemistry concepts, as this method enhance students achievement and reduce students anxiety.